The Movie business book - Squire, Jason E. 1948- (New York Simon & Schuster, 1992)
In The Movie Business Book, forty of Hollywood's most celebrated producers, directors, screenwriters, agents, lawyers, marketers, distributors, exhibitors, and deal makers reveal the secrets of their trade in personal accounts that are both highly informative and wonderfully entertaining.

This new edition--fully revised and updated for the movie industry of the 90's--includes such unique perspectives as David Puttnam on producers, Sydney Pollack on directors, Henry Jaglom on independent filmmaking, Mike Medavoy on studio management, Richard Childs on home video, Martin Polon on new technology, and thirty-four more.
"A Fireside book."
Includes index (471-479 pages).
Keywords: Motion picture industry -- United States